Stability of finger millet genotypes under diverse environments - Sood, Salej; Patro, T. S. S. K.; Karad, Sunil; Sao, Abhinav (The Indian Journal of Genetics and Plant Breeding, 2016)
The present study aimed at deciphering the stability and patterns of genotype × environment interaction (GEI) in finger millet genotypes tested in All India Coordinated Trials using GGE biplot technique. The combined ANOVA for grain yield of five finger millet cultivars at four environments showed that environments (E), genotypes (G) and GEI were highly significant (P<0.01). GGE biplot grouped the four environments into two mega environments with GPU 67 and VR 990 as winning genotypes. VL 376 was found to be an ideal genotype in terms of high yield and stability followed by VR 990 as desirable genotype.